Ahmedabad Library Network-ADINET - Thakore, S.R. (DESIDOC Journal of Library & Information Technology, 2002)
The paper describes the databases being developed by ADINET and the information and communication services it presently offers and plans to offer in the near future to its member libraries and other users. ADINET, although a very recently started network formally inaugurated in February 1995), has taken quitwe a few initiatives to play a very useful roled in library resource sharing and in information dissemination. http://dx.doi.org/10.14429/dbit.16.2.3257